Альтернативные источники энергии в Республике Казахстан - Иманбаева, А.Б. (My University, 2013)
This article deals with the problem of the current state and development of alternative energy sources in the Republic of Kazakhstan. Much attention is paid to the geography of the development of wind, solar energy and hydropower.